The Reproductive Platform to Deliver Genetic Gain in Sheep and Goats - Rekik, Mourad; Getachew, Tesfaye; Rischkowsky, Barbara A.; Abate, Zelalem; Besufekad, Shanbel; HabteGiorgis, Kebede; Wondim, Bekahegn; Jimma, Addisu; Dea, Dereje; Jenbere, Temsegen; Routabi, Myriam; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2022)
The Reproductive Platform to Deliver Genetic Gain in Sheep and Goats presentation.